As certificações como instrumento ético de sustentabilidade ambiental em edificações da construção civil - Silva, Givaldo Barbosa da (2014)
This research is focused on environmental certifications for buildings as a tool of sustainability from the perspective of environmental ethics. The intention is to contribute to the advancement of knowledge in the field of construction, particularly in its modernization through sustainability certificates in Brazil, and observe how this methodology can contribute to improving the environmental quality of urban spaces. Thus, the thesis was structured basically in five chapters or approaches. The first chapter, which has a theoretical approach, focuses on three analytical categories: nature, ethics, and environmental sustainability, which together form the conceptual ballast connection between all treated subjects. The concept of nature was analyzed from modernity, seeking to understand how this came to determine the course of human existence and as entered in society and urban space. Here, the study of ethics is centered on the challenge of solving contemporary dilemmas facing the techno-scientific advances in the struggle between man and environmental damage. The theme of environmental sustainability is built in questioning of several senses involving this issue in the counterpoint between sustainability and sustainable development, to establish its extensions, overlaps and differences between these two concepts. The second chapter deals with the construction of the sustainable city space, from its historical / urban bases to the influence of legal frameworks for their training. The third chapter investigates the response of the building industry to new environmental challenges posed by the scarcity of natural resources, the possibilities of rearrangement of their production chain and their union. The fourth deals with LEED, AQUA, ProcelEdifica e Casa Azul certifications, how it is being widespread in the country, its limits and scope.Finally, in the fifth and final chapter, there are two findings: first, we sought to demonstrate, through a comparative framework, the limited capacity of these four assessment methodologies to certify the sustainability of buildings, fitting them into two groups, namely, Environmental Certifications (Leed e ProcelEdifica) and Social and Environmental Certifications (AQUA and Casa Azul); second, we present an alternative instrument to the certifications for those who do not want or cannot link to a certifying institution but that still want to get recognition for their sustainable building practices, this instrument grounded in environmental ethics.